EFFECT OF DRY NEEDLING ON PAIN AND CERVICAL RANGE OF MOTION IN PATIENTS WITH UPPER TRAPEZIUS TRIGGER POINTS: A SYSTEMATIC REVIEW - POONAM ROKRI; PRABHAT KUMAR; SHARVIL DHAR; HITANSHU AGNIHOTRI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: This systematic review seeks to provide high-quality evidence on the effect of dry needling on cervical range of motion and pain in patients. The objective of this systematic review was to determine the evidence base for the effect of dry needling on cervical range of motion and pain in patients with upper trapezius trigger points. Material and methods: A systematic electronic literature search was undertaken utilizing keywords and medical subject heading search phrases in the PubMed/Medline, Cochrane Central, Scopus, and EBSCO databases, as well as Google Scholar. In addition, the reference lists of the systematic reviews included in the study were manually searched. Patient satisfaction and complications were collected from a range of motion prospective and experimental studies that provided the greatest degree of evidence. Articles were evaluated critically, and the methodological index for non-randomized studies scale was used to determine the risk of bias. Results: This systematic review suggested the use of dry needling to improve pain and functional capacity in patients with chronic neck pain at short- and mid-term intervals. To the interventions, dry needling combined with physical therapy was shown to be effective in decreasing pain, whereas isolated dry needling did not demonstrate significant improvements in the analyzed studies. Conclusion: Finally, as for pain, dry needling combined with physical therapy was the therapy that showed the most benefits in function in the analyzed studies